2012
DOI: 10.1371/journal.pone.0051870
|View full text |Cite
|
Sign up to set email alerts
|

The Anorectic Effect of GLP-1 in Rats Is Nutrient Dependent

Abstract: GLP-1-induced insulin secretion from the β-cell is dependent upon glucose availability. The purpose of the current study was to determine whether CNS GLP-1 signaling is also glucose-dependent. We found that fasting blunted the ability of 3rd cerebroventricularly (i3vt)-administered GLP-1 to reduce food intake. However, fasted animals maintained the anorexic response to melanotan II, a melanocortin receptor agonist, indicating a specific effect of fasting on GLP-1 action. We also found that i3vt administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…However, a thorough analysis of meal pattern has not been done and it is possible that GLP-1 can have effects on meal size and duration, consistent with other gut peptides, such as CCK. Consistent with other studies, we have recently demonstrated that peripheral, native GLP-1 requires either a postprandial state or an ongoing meal to induce satiation (59,(63)(64)(65). Prolonged fasting attenuates the satiating effects of GLP-1.…”
Section: Glp-1 and The Control Of Food Intakesupporting
confidence: 90%
“…However, a thorough analysis of meal pattern has not been done and it is possible that GLP-1 can have effects on meal size and duration, consistent with other gut peptides, such as CCK. Consistent with other studies, we have recently demonstrated that peripheral, native GLP-1 requires either a postprandial state or an ongoing meal to induce satiation (59,(63)(64)(65). Prolonged fasting attenuates the satiating effects of GLP-1.…”
Section: Glp-1 and The Control Of Food Intakesupporting
confidence: 90%
“…Also, infusion of GLP-1 was insufficient to significantly reduce food intake or modulate neural responses to visual food cues, whereas GLP-1 in combination with peptide YY(3–36) did suppress food intake and regional brain activation (De Silva et al, 2011). Moreover, w hen glucose utilization in the central nervous system is blocked, the anorectic effect of intraventricular GLP-1 is diminished (Sandoval et al, 2012). In sum, GLP-1 infusion or receptor stimulation appears to be sufficient to promote meal-related satiety in humans in a dose-dependent manner (Verdich et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…shrew and ferret) will collectively deepen our understanding of the neurobiological mechanisms of emesis/nausea/malaise induced by GLP-1 and amylin-pharmacology. Indeed, in the case of GLP-1, we (84) and others (95; 166) have suggested that the field as a whole must utilize a multi-model approach to disentangle physiological (e.g. regulation of food intake and blood glucose) and pathophysiological (e.g.…”
Section: Pathophysiological Effects Of Amylin- and Glp-1-based Phmentioning
confidence: 99%